Scale up study on production of biodiesel from Jatropha crude oil - Mohd Taufiq, Rasdi (2013)
Scale up is a very important activity in designing new industrial plants especially in specialty or fine chemicals production. The purposes of this study is to study on different between laboratory scale production and pilot plant production of biodiesel from Jatropha crude oil and to establish correlations between laboratory scale and pilot plant scale for construction of commercial plant. Transesterification process used KOH as a catalyst. The optimum quantity of methanol, catalyst KOH, reaction temperature and reaction time required for the transesterification of Jatropha oil were conducted by varying them. Then, the optimized conditions from laboratory scale were used in pilot plant scale. From this study, it was found that for laboratory scale and pilot plant scale, there are some differences in the value of the final yield. The difference of value of yield between the laboratory scale and pilot plant run was caused by several factors such as handling, operating conditions and others.